SOMATISMS IN THE OLD TATAR LANGUAGE - Mukhametova, Ilkhamiya I.; Kadirova, Enze Kh; Yusupov, Ayrat F.; Alkaya, E. (Univ Estado Rio Grande Norte, 2019)
The article is devoted to the study of the lexical system of the Old Tatar language and the identification of the style-forming properties of lexical means in the language of fiction. The analysis reveals the patterns of somatism functioning in the structure of poetic texts of this period. The written sources of this period recorded rich Turkic-Tatar lexical material with synonymous series, idiomatic constructions reflecting the most diverse aspects of the social, economic way of life of that time, cattle breeding and agriculture, the animal and plant world, human and animal anatomy, crafts and human activities. In this work, the somatic vocabulary of Old Tatar texts is analyzed. The words denoting the names of human body parts are the most common in the Old Tatar language. In this work, the study of somatisms is performed at the lexical and phraseological levels. The names of human body parts, especially phraseological material with somatisms, are of great interest to modern researchers. The authors of this article cite a number of observations on the nature of phraseological somatisms and their behavior in context. All statements are illustrated by examples from the monuments of the Old Tatar language. Attention is focused on the functioning of phraseological units with components-somatisms in diachrony.
Keywords: Tatar language; Old Tatar language; written monuments; somatisms; phraseological units; vocabulary